Population subdivision in the tropical spiny lobster Panulirus ornatus throughout its Indo-West Pacific distribution. (28th October 2016) - Yellapu, Bhargavi; Jeffs, Andrew; Battaglene, Stephen; Lavery, Shane D.
Abstract : Many marine species with Indo-West Pacific distributions have been found to have a considerable level of genetic population structuring across this broad region. We investigated mitochondrial DNA diversity throughout the extensive range of the commercially valuable ornate spiny lobster, Panulirus ornatus, which has an unusually lengthy larval period that can last up to six months. In this study, 298 specimens were sampled from 17 locations covering the West Indian Ocean, Western Australia, Southeast Asia, and the Northwest and Southwest Pacific. Based on sequencing of a 461 bp fragment of mitochondrial control region, we found high levels of haplotype diversity ( H = 0.99) and overall significant population differentiation (Φst = 0.113, P < 0.001). The West Indian Ocean and Western Australia populations were the most genetically divergent, with little differentiation among the remaining Southeast Asian and West Pacific populations. The Western Australia population showed evidence of being a peripherally isolated population, with significantly lowered effective population size, likely due to the prevailing ocean currents. The present results indicate that genetically distinct stocks of P. ornatus are present in the wild and that historical and present day biogeographic phenomena have likely influenced this population structure. The presence of these divergent stocks has major implications for both management of fisheries and aquaculture breeding programs for this valuable species.